1999
DOI: 10.1002/(sici)1096-9861(19990628)409:2<313::aid-cne11>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Central melatonin receptors in the rainbow trout: Comparative distribution of ligand binding and gene expression

Abstract: To better define the role of melatonin in fish, we have compared in detail the distribution of 2‐[125I]iodomelatonin binding sites with gene expression for melatonin receptor subtypes in a widely studied seasonal species, the rainbow trout. Three distinct partial sequences of the melatonin receptor gene were cloned from trout genomic DNA. Two of the sequences corresponded to the Mel1a receptor subtype, and one corresponded to the Mel1b receptor subtype. Analysis of numerous clones failed to find a sequence equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
67
3
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 56 publications
11
67
3
5
Order By: Relevance
“…The demonstration of changes in brain dio2b expression in sites remote from the pituitary or SV and the lack of evidence for extra-pituitary sites of TSH expression suggest that additional upstream pathways must be sought. One possibility that merits further attention, based on similarities in melatonin receptor distribution in the brain of another migratory salmonid (the rainbow trout, Oncorhynchus mykiss) [32] and dio2b gene expression in S. salar in the present study, is that melatonin mediates photoperiodic effects on brain dio2b expression during smoltification.…”
Section: Discussionmentioning
confidence: 78%
“…The demonstration of changes in brain dio2b expression in sites remote from the pituitary or SV and the lack of evidence for extra-pituitary sites of TSH expression suggest that additional upstream pathways must be sought. One possibility that merits further attention, based on similarities in melatonin receptor distribution in the brain of another migratory salmonid (the rainbow trout, Oncorhynchus mykiss) [32] and dio2b gene expression in S. salar in the present study, is that melatonin mediates photoperiodic effects on brain dio2b expression during smoltification.…”
Section: Discussionmentioning
confidence: 78%
“…To the best of our knowledge, precise data of Per2 daily expression are not available in Wsh diencephalon, but Per1 transcripts also peaked in the rainbow trout hypothalamus during daytime at ZT3 (Patiño et al 2011). The diencephalon and the optic tectum receive or integrate information from sensory organs in teleost Wsh (e.g., retinal and pineal projections) and contain high concentration of melatonin receptors in most species including sole (Confente et al 2010;Herrera-Perez et al 2010;Mazurais et al 1999;Oliveira et al 2008). In addition, as mentioned before, Per2 is light-inducible in Xenopus, zebraWsh, quail, and mammals, and it has been shown that some diencephalic areas are photosensitive in diVerent non-mammalian vertebrates Kojima et al 2000;Menaker et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to clone melatonin receptors in fish, and a few partial sequences have been obtained from zebrafish (Danio rerio), pike (Esox lucius) and trout (Oncorhynchus mykiss); not only have the MT1, MT2 and Mel1c receptors been found, but there is an indication that several copies of each might exist in the zebrafish [24][25][26][27]. The three full-length sequences obtained to date correspond to trout MT1 (accession number AF156262), rabbitfish (Siganus guttatus) MT1 (accession number DQ768087) and pike MT2 (accession number AF188871) [25].…”
Section: Box 2 Daily Locomotor and Feeding Activity Rhythms In Fishmentioning
confidence: 99%
“…In fish, melatonin receptors have been detected in all of the different brain areas and the retina, and the relative expression of each subtype varies from one area to another [24,26,29]. In lampreys, chondrichthyans and teleost fish, gene expression or 125 IMel binding are associated with areas that receive or integrate information from sensory organs (e.g.…”
Section: Melatonin Receptors and The Integration Of Photoperiodic Infmentioning
confidence: 99%